Immunoglobulin-Y Effect On Protein Of Streptococcus Mutans Isolated From Caries And Caries-Free Subjects - Rizky Aditiya Irwandi; Endang Winiati Bachtiar; Mindya Yuniastuti (Universitas Muhammadiyah Yogyakarta, 2012)
The main microbial culprit in dental caries is Streptococcus mutans (S.mutans), virulence of which can be observed by its differential protein expression between caries and caries-free subjects.The success of Immunoglobulin-Y (IgY) anti S.mutans as a passive immunization agent in eliminating S.mutans has been reported. The aim of this study is to analyze the effect of IgY anti S.mutans on the protein expression of S.mutans isolated from caries and caries-free subjects. Each dental plaque was collected by swabbing the buccal surface of the first lower permanent molar of caries and caries-free subjects. The plaques were then cultured on agar medium TYS20B. After 72 hours, the colonies from each of them were cultured in liquid medium TYS Broth for 72 hour. Each collected bacteria (whether from caries or caries-free subjects) were grouped into control and exposure group. In exposure group, S.mutans was exposed by pre-incubated (for one hour at 37°C) IgY anti S.mutans for one hour at 37°C. Protein expression of S.mutans was analyzed with SDS PAGE after the preparation of its antigen and Bradford protein assay. Our result shows that S.mutans 41.3 kilodalton protein expression of caries subjects, are up-regulated in comparison to the control group. Meanwhile, the S.mutans 41.3 kilodalton protein expression of caries-free subjects, are down-regulated in comparison to the control group. This study suggests that IgY anti S.mutans up-regulates 41.3 kilodalton protein expression of S.mutans in the caries subjects. However IgY anti S.mutans down-regulates 4.13 kilodalton protein expression of S.mutans in the caries-free subjects.